Enhancing the Creditworthiness of Municipal Bonds : Innovations from Mexico - Leigland, James; Mandri-Perrott, Cledan (World Bank, Washington, DC, 2012)
In 2001-03 the municipal bond market in Mexico was among the most active in the developing world. Government officials had found a way to dramatically enhance the creditworthiness of local government debt without using sovereign guarantees. The technique, adapted in part from private sector 'future flow' financing deals, enabled a state or local government to earn significantly higher credit ratings for bond issues than for its normal balance sheet debt. Many other developing countries have turned to Mexico as a source of innovation that may have application in their own markets.